Contradictions Regarding Innovations and Certifications in the Bioenergy Sector in Argentina - Toledo-López, Virginia (2019)
The article investigates the innovations within the bioenergy sector in Argentina in order to analyze their contribution to the modernization of agriculture and the expansion of the current accumulation regime. The socio-territorial and environmental impacts of those innovations are discussed, as well as their contradictions, focusing on particular cases. Discourse analysis allows to see how these innovations are embedded in sustainability conceptions, in the context of ecological modernization. The article identifies their structuring arguments, reconstructs their conceptual frame and narratives, and explores their contradictions and silences. Therefore, it reflects on the sense of these innovations in the bioenergy sector in Argentina, presenting them as mechanisms that contribute to green grabbing, given that the environmental approach serves as an excuse for new markets and capital expansion.